Towards an Increased Detection Sensitivity of Time-Delay Attacks on Precision Time Protocol - Lea Schonberger (IEEE, 2021)
Precision time protocol (PTP) is one of the most widely used protocols for clock synchronization in packet-switched networks, on which, among others, the transaction synchronization of the stock markets relies. PTP was not standardized with security as a core requirement and is therefore vulnerable and attractive to manifold kinds of malicious attacks, such as time-delay attacks (TDAs). TDAs, in short, corrupt the exchange of timestamped messages and thus cause an incorrect synchronization process. The annex P of the IEEE 1588-2019 standard has defined a number of security mechanisms for clock synchronization, but, however, none of these can protect a PTP-based system completely against TDAs. In this work, we enhance existing approaches by introducing a so-called observation task and analytically deriving attack parameters of an ongoing TDA. Following the recommendation of the annex P of the IEEE 1588-2019 standard, these attack parameters can serve as an additional input for intrusion detection systems and allow for a more reliable and sensitive detection of TDAs. In a comprehensive evaluation, we experimentally investigate the impact different attack parameter combinations can have on a system.